Challenges encountered in high-lift block cave extensions and the lessons learned: experience from the Padcal Mine, Philippines - Monis, J.A.; Palma, B.; Villarin, V.; Lim, A. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The Padcal Mine in northern Philippines has operated using block caving since 1963 and continues to extend production into deeper and peripheral ore zones through high-lift block cave development. Since 2021, recurring rockburst events have been recorded during the development and early commissioning of the 798 mining level blocks, particularly within high-lift extensions located at the margins of the active cave footprint. These areas are characterised by abutment stress concentrations and complex stress redistribution associated with staged cave expansion. This paper documents the challenges encountered during the development and commissioning of high-lift block cave extensions, with emphasis on seismic response, ground support performance, dilution control, and block development layout and sequencing. Lessons learned from Padcal highlight the critical role of abutment stress management, the importance of drawpoints connectivity, the limitations of conventional support systems under dynamic loading, and the need for adaptive draw control, undercutting, and development strategies. Mitigation measures implemented include enhanced active support reinforcement, blasting deferment protocols, draw control strategies, and the use of isolation crosscuts to manage cave expansion risks and to achieve successful block commissioning. The outcomes offer practical, experience-based guidance for planning, commissioning, and operating highlift block cave extensions in similarly stressed and seismically active environments.